If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(m) = m + 4 Multiply f * m fm = m + 4 Reorder the terms: fm = 4 + m Solving fm = 4 + m Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'm'. f = 4m-1 + 1 Simplifying f = 4m-1 + 1 Reorder the terms: f = 1 + 4m-1
| -37+x=123 | | 2x+12=-7x-19 | | 3(4+w)=3(w+4) | | f(10)=0.08x^3+x^2+x+0.26 | | 9x-3+5x+8=15x | | -2(1+6x)-3= | | 3x+12=69 | | 11=2(w-2)+2w | | 10b-10=9b | | -5(9p-4)= | | 48n^2-6=-42n | | f^2+g^2=2fg | | -10x+3=-17 | | 3x-9=10x-30 | | 63=3u | | 2x+12=2x-19 | | 3e=27 | | 1/5=10/50 | | 3-18+4m=m | | 10=v-9 | | b-1+4=b-1 | | 16-16xsquared=0 | | 115+24x-5=90 | | 100*y=2.2973 | | 10r+2=3(r+4) | | y-9=-7 | | 6+15n=17n+26 | | m+9=91 | | 4(x+6)=2(7x+1) | | 440=3(w-60)+2w | | x-.22x=506.61 | | 3m+2n=-2 |